Economic Viability of Waste-to-Energy: Pathways for Sustainable Power Generation in Jalingo, Taraba State, Nigeria - Koliya LAAYE; Solomon O. OGUCHE; Ibrahim I. JIDDA; Abdullahi A. ADAMU (FUDMA Journal of Engineering and Technology, 2025)
This study evaluates the technical and economic viability of waste-to-energy (WtE) technologies for sustainable electricity generation in Jalingo metropolis, Taraba State, Nigeria. Two WtE pathways were assessed: (i) thermal conversion through incineration with power generation, and (ii) landfill gas (LFG) capture with reciprocating engines. Locally reported municipal solid waste (MSW) data and performance-cost ranges from literature were applied to estimate electricity potential, installed capacity, levelized cost of electricity (LCOE), net present value (NPV), and internal rate of return (IRR). The waste composition was dominated by plastics (29.67–34.67%) and agricultural residues (28–29%), followed by paper/cardboard (9.88–11.93%), textiles (4.04–9.20%), and food waste (5.66–6%). Metals (0.42–1.11%) and glass (0.90–1.30%) constituted the smallest fractions. Moisture content ranged from 25.40% at Mile Six dumpsite to 28.98% at Pantinapu; volatile matter peaked at 38.84% at Mile Six. Heat values between 6.32 and 6.68 MJ/kg confirmed the technical feasibility of incineration-based energy recovery. Electricity generation potential was estimated at 39,417.74 kWh/day from incineration and 1,644,106.24 MWh/year (≈4.5 million kWh/day) from LFG, capable of supplying approximately 17,127 and 1,957 households respectively, based on average household consumption of 840 kWh/year. Economic analysis revealed positive NPVs (1.20–1.45 million) and IRRs of 18–79% at a tariff of N250/kWh (US 0.15), demonstrating profitability. Environmental assessment indicated that methane combustion for electricity reduced carbon dioxide emissions by about 88.18% compared to uncontrolled waste disposal. The findings highlight that municipal solid waste in Jalingo possesses sufficient energy content to support WtE initiatives. Both incineration and LFG capture not only offer substantial electricity generation potential but also present economically viable and environmentally sustainable alternatives to current waste management practices.